Transcatheter or Surgical Aortic Valve Replacement in patients with Severe Aortic Stenosis Aged 70 Years or Younger - a NOTION-2 sub-study - Jørgensen, Troels Højsgaard; Thyregod; Hans Gustav Hørsted; Savontaus, Mikko; Bleie, Öjvind; Christiansen, Evald H; Niemelä, Matti; Angerås, Oskar; Gudmundsdóttir, Ingibjörg J.; Laine, Mika; Rück, Andreas; Prendergast, Bernard; et al. (Elsevier BV, 2025)
This NOTION-2 sub-study revealed distinct outcomes for transcatheter aortic valve replacement (TAVR) and surgical aortic valve replacement (SAVR) in low surgical risk patients aged ≤ 70 years with a tricuspid or bicuspid aortic valve stenosis (AS). One year after intervention, the risk of death, stroke or rehospitalization in patients with tricuspid AS was similar after TAVR when compared to SAVR (absolute risk difference: -2.0%; 95% confidence interval (CI): -11.8% to 7.7%) Conversely, in patients with bicuspid AS, TAVR was associated with a significantly higher risk of adverse outcomes (absolute risk difference: 13.8%; 95% CI: 1.2% to 26.3%). These analyses are exploratory, but highlight the importance of tailoring the intervention to the patient's clinical risk profile, life expectancy, native aortic valve morphology and the anticipated risks associated with TAVR or SAVR.